2012
DOI: 10.1021/jp308614k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-Induced Modification of Surface Electronic Structure: Pyrocatechol Adsorption on the Anatase TiO2 (101) and Rutile TiO2 (110) Surfaces

Abstract: Photoemission and near-edge X-ray absorption fine structure (NEXAFS) techniques have been used to study the adsorption of pyrocatechol on anatase TiO 2 (101) and rutile TiO 2 (110) single crystals. Photoemission results suggest the pyrocatechol molecule adsorbs on both surfaces predominantly in a bidentate geometry. Using the searchlight effect, the carbon K-edge NEXAFS spectra recorded for pyrocatechol on anatase TiO 2 (101) and rutile TiO 2 (110) show the phenyl rings in the pyrocatechol molecule to be orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 58 publications
10
75
1
Order By: Relevance
“…This presents a much clearer picture of the temperature-dependent changes in the adsorbate’s molecular orbital structure. In the room temperature spectrum (black), the shoulder on the TiO 2 valence band is revealed as a distinct peak at 3 eV, very similar to that reported for catechol on rutile TiO 2 (110) though approximately 0.6 eV higher in binding energy 24,25 . With reference to the spectrum of multi-layer physisorbed phenol at low temperature (pink) and the calculated molecular orbitals of an isolated phenol molecule (see also Fig.…”
Section: Resultssupporting
confidence: 74%
“…This presents a much clearer picture of the temperature-dependent changes in the adsorbate’s molecular orbital structure. In the room temperature spectrum (black), the shoulder on the TiO 2 valence band is revealed as a distinct peak at 3 eV, very similar to that reported for catechol on rutile TiO 2 (110) though approximately 0.6 eV higher in binding energy 24,25 . With reference to the spectrum of multi-layer physisorbed phenol at low temperature (pink) and the calculated molecular orbitals of an isolated phenol molecule (see also Fig.…”
Section: Resultssupporting
confidence: 74%
“…But it is yet unclear if it is a monodentate adsorption (only one dopamine oxygen is linked to one Ti), bidentate adsorption (both oxygen sites linked to adjacent Ti atoms) or chelated adsorption (both oxygen sites adsorbed on the same Ti). NEXAFS experiments on isolated dopamine and dopamine on anatase TiO 2 (101) 12 and rutile (110) 13 showed that the molecule interacts strongly with the surface, in agreement with theoretical calculations.…”
Section: Introductionsupporting
confidence: 82%
“…Finally,c ombined DFT and STM studies [65] showed that isolated catechols tend to adsorb as ab ridging bidentate structure parallel to the Ti 5c rows on the rutile surface,w ith the benzene ring perpendicular to the surface plane.T his study also demonstrated the ability of catechols to readily exchange protons with surrounding oxygen atoms,a llowing them to move across the surface.B eyond demonstrating the diffusion capacity of these molecules on rutile,t hese results also brought relevant information about the above-mentioned interconversion between monodentate and bidentate coordination structures. [34] Another interesting study by Grätzel and co-workers [66] compared the adsorption of pyrocatechol on an anatase (101) single crystal and the crystallographically equivalent rutile (110). Theauthors deposited the catechol by evaporation and characterised it by XPS and near-edge X-ray absorption finestructure (NEXAFS) experiments.T he authors crosschecked the collected data with DFT-optimised geometries to conclude that pyrocatechol binds more strongly to the anatase surface than to the rutile surface.A dditionally,s pectra obtained for O1ss uggested that pyrocatechol adsorbs predominantly at high coverages on both surfaces with ab identate geometry ( Figure 4);b oth pyrocatechol O atoms are chemically equivalent as they appear as only one strong peak (at 531.9 eV for anatase and 531.3 eV for rutile).…”
Section: Chemical Bonding 221 Coordinationmentioning
confidence: 99%